RETRACTED: The significance of creating embroidery patterns from art decoration techniques in the field of sewing - knitting - Mamatkulova Saida; Berdyeva Rano; Obidova Irodakhon; Khoshimova Maftuna; Rakhmonova Malohat; Mominov Bekzod (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001